GENETIC VARIABILITY FOR YIELD AND QUALITY TRAITS IN GINGER (ZINGIBER OFFICINALE ROSCOE) - RAVISHANKER; KUMAR, SANTOSH; A. CHATTERJEE; D. K. BARANWAL; S. S. SOLANKEY (The Bioscan, 2013)
The genetic variability, heritability, genetic advance and correlation coefficient were estimated for yield and quality traits in twenty five ginger germplasm. Wide genetic variation was observed for all genotypes for yield per plant, plant height and days taken to harvest. Considering genetic parameters, high GCV was found highest for acidity (42.94%) followed by oleoresin content (37.50%), ascorbic acid content (34.78%) and yield per plant (23.81g), respectively. In all cases, phenotypic variances were higher than the genotypic variances. Based on high heritability coefficient (h2 b.s.) coupled with high genetic advance as % of mean, oleoresin content (0.98, 76.36%), ascorbic acid content (0.97, 70.42), acidity % (0.93, 85.45%), TSS per cent (0.90, 43.71) and yield per plant (0.87, 45.69) were found superior traits and representing additive genetic variance. Effective selection would be made considering these traits. Genotypic correlation coefficient revealed that rhizome yield had significant positive correlation with length of primary finger (0.40), ascorbic acid content (0.37), number of primary fingers (0.35), plant height (0.36) and diameter of primary finger (0.31).